Mutualistic networks emerging from adaptive niche-based interactions - Weiran Cai; Jordan Snyder; Alan Hastings; Raissa M. D’Souza (Nature Communications, 2020)
Nested and modular patterns are vastly observed in mutualistic networks across genres and geographic conditions. Here, the authors show a unified mechanism that underlies the assembly and evolution of such networks, based on adaptive niche interactions of the participants.